Disproportional voting rights and shareholder wealth: the evidence from the US dual class firms - Luo, Jiannan (2018)
I use a unique sample of 617 U.S. firms adopting the dual class structures for at least a period of their lifetime from 1994 to 2013 to examine the relation between the presence of disproportional voting rights and outside shareholder wealth. I find that the presence of restricted-voting shares is insignificantly related to the buy-and-hold-abnormal returns for the windows of 1-, 3- and 5-year after the initial public offerings. In addition, the presence of dual class structures would reduce a firm’s probability of being taken over by around 20% but would not increase the amount of takeover premium conditional on the successful takeover. Theses empirical findings are consistent with the theoretical prediction that dual class structures may have both positive and negative impact upon shareholder wealth and it is difficult to tell whether the positive or the negative impact prevails. Practically, the finding implies that, for policy makers, the decisions to allow for or abolish dual class structures may depend on the country’s legal environment.